ChemInform Abstract: A Strategy Towards the Multigram Synthesis of Uncommon Hexaarylbenzenes. Issue 35 (11th August 2016) - Lungerich, Dominik; Reger, David; Hoelzel, Helen; Riedel, Rene; Martin, Max M. J. C.; Hampel, Frank; Jux, Norbert
Abstract: The strategy for the synthesis of hexaarylbenzenes avoids regioisomeric product distributions.